Understanding Sharia Values on Islamic Bank Community in Makassar - Suriyanti; Amir; Ajmal As'ad (Jurnal Manajemen Bisnis, 2021)
This research aims to how the reality of the existence of Islamic banks in transforming spiritual values ​​(Islamic ethics) both micro (organizational) and macro (wider society) so that there is an internalization of value in the economic activities of the community. From this understanding can be spelled out through the formulation of the problem. This study uses an interview technique of 100 samples where we ask managers and staff who work in Islamic banks to answer several questions and questionnaires that we have created. This study also uses a qualitative approach so that the researcher concludes the results of the interviews that have been conducted in compiling research findings. The results of the study indicate that the Islamic values ​​applied to Islamic banks have not been implemented properly. There are still some conventional values ​​applied to the bank.